Does Aging at Home Make Older Adults Healthy: Evidence from Medicaid Home and Community-Based Services - Yinan Liu; Xianhua Zai (Global Labor Organization (GLO), 2022)
The Medicaid Home and Community-Based Services (HCBS) subsidizes long-term care to satisfy the increasing desire to age at home among older adults. The HCBS program may improve health outcomes of this population by allowing them to age-in- place, but less quality and quantity of home-based care comparing to nursing home care could offset some of the potential benefits. We use plausibly exogenous policy expenditure across states over time linked with detailed health information from the restricted Health and Retirement Study (HRS) to identify the causal effects of HCBS on general health, physical health, and mental health of older adults. Overall, our findings suggest that HCBS is beneficial to health: a 1,000 increase in HCBS per older person improves health status by 6 percent, mitigates functional mobility limitations by 5 percent, and reduces negative psychological feelings by 10 percent. The positive effect on physical health is concentrated among people with limited financial resources, while the reducing impact on mental health is significant among the richer group. The HCBS program improves health outcomes mainly through three mechanisms: decreasing risk behavior on drinking, increasing healthcare use, and spending more time accompanying with family.
Keywords: I12; I18; I30; 330; Medicaid HCBS; Long-Term Care; Health; Aging